2005
DOI: 10.1258/0022215054352135
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ referral pattern for children with acute facial paralysis

Abstract: Of the GPs surveyed 78 per cent did not refer children presenting with acute facial paralysis to an otolaryngologist. We suggest minimum investigations for acute facial paralysis in children before diagnosing Bell's palsy and stipulate otolaryngology referral for all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Despite a lot of similarities concerning pathogenesis, treatment, and outcome there are also some important differences. Facial nerve palsy appears 2–4 times less frequent in children than in adults [ 33 ]. Additionally, facial nerve palsy appears to be more frequently associated with viral infection and with Borreliosis than in adults [ 34 , 35 ].…”
Section: Childrenmentioning
confidence: 99%
“…Despite a lot of similarities concerning pathogenesis, treatment, and outcome there are also some important differences. Facial nerve palsy appears 2–4 times less frequent in children than in adults [ 33 ]. Additionally, facial nerve palsy appears to be more frequently associated with viral infection and with Borreliosis than in adults [ 34 , 35 ].…”
Section: Childrenmentioning
confidence: 99%
“…13 Bell's palsy is different from other facial palsies as the cause is metabolic or vascular. 14 In cases associated with idiopathic cause (Bell's palsy), ENT examination is essentially normal and majority of patients show good recovery with treatment with steroids, anti-viral drugs and physiotherapy. In cases of otitis media associated with cholesteatoma where mastoidectomy is done and facial nerve is explored, good recovery is observed in cases associated with perifacial granulation tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, there is an incidence of 6.6 per 100 000 people in the 0–14-year age bracket 5. This incidence is likely to be an underestimation, as many mild cases may be seen by a general practitioner and not included in the total incidence 6. El-Hawrani et al 6 found that only 22% of children presenting with acute facial nerve paralysis (FNP) were referred to an otolaryngologist.…”
Section: Introductionmentioning
confidence: 99%
“…This incidence is likely to be an underestimation, as many mild cases may be seen by a general practitioner and not included in the total incidence 6. El-Hawrani et al 6 found that only 22% of children presenting with acute facial nerve paralysis (FNP) were referred to an otolaryngologist. They and others suggested that all children presenting in the community with acute BP should be referred to an otolaryngology unit for further investigations and acute management 4 6–8…”
Section: Introductionmentioning
confidence: 99%